2021
DOI: 10.1177/10732748211053567
|View full text |Cite
|
Sign up to set email alerts
|

Acral Lentiginous Melanoma: A United States Multi-Center Substage Survival Analysis

Abstract: Background Acral lentiginous melanoma is associated with worse survival than other subtypes of melanoma. Understanding prognostic factors for survival and recurrence can help better inform follow-up care. Objectives To analyze the clinicopathologic features, melanoma-specific survival, and recurrence-free survival by substage in a large, multi-institutional cohort of primary acral lentiginous melanoma patients. Methods Retrospective review of the United States Melanoma Consortium database, a multi-center prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
1
9
2
Order By: Relevance
“…8,10,26,27 Recent studies focused on AM have shown that in the absence of nodal disease tumor thickness of >2 mm 2 are more likely to experience disease recurrence. 19,28,29 Comparing all anatomic sites and histological subtypes of cutaneous melanomas at the pathologic stage T1 (Breslow thickness ≤1.0 mm), AM histologically classified as acral lentiginous melanoma (ALM) was associated with lower 5-and 10-year overall survival, disease-specific survival, and DFS rates. 10 It is important to highlight that, in this study, the term AM refers to cutaneous melanoma occurring on acral skin (glabrous skin of the soles, palms, and nail bed), regardless of whether the histological subtype is ALM or not.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,10,26,27 Recent studies focused on AM have shown that in the absence of nodal disease tumor thickness of >2 mm 2 are more likely to experience disease recurrence. 19,28,29 Comparing all anatomic sites and histological subtypes of cutaneous melanomas at the pathologic stage T1 (Breslow thickness ≤1.0 mm), AM histologically classified as acral lentiginous melanoma (ALM) was associated with lower 5-and 10-year overall survival, disease-specific survival, and DFS rates. 10 It is important to highlight that, in this study, the term AM refers to cutaneous melanoma occurring on acral skin (glabrous skin of the soles, palms, and nail bed), regardless of whether the histological subtype is ALM or not.…”
Section: Discussionmentioning
confidence: 99%
“…In general, AM has a worse outcome compared with non‐acral cutaneous melanoma 8,10,26,27 . Recent studies focused on AM have shown that in the absence of nodal disease (i.e., stage I‐II), the prognosis is worse in acral melanoma patients with higher Breslow thickness tumors compared with cutaneous melanoma in all disease stage, and patients with a tumor thickness of >2 mm 2 are more likely to experience disease recurrence 19,28,29 . Comparing all anatomic sites and histological subtypes of cutaneous melanomas at the pathologic stage T1 (Breslow thickness ≤1.0 mm), AM histologically classified as acral lentiginous melanoma (ALM) was associated with lower 5‐ and 10‐year overall survival, disease‐specific survival, and DFS rates 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study with ALM patients, the 5- and 10-year DSS rates were higher in women than in men ( p < 0.001), and men were more likely to develop thicker tumors than women ( p < 0.001). Moreover, men had later disease staging than women ( p < 0.001) [ 19 ], as described by Phan, Kolla, and Huang et al [ 4 , 20 , 21 ]. Additionally, in a study of melanomas located in the lower limbs, the frequency of disease progression was higher in men than in women, regardless of whether the site of disease was in the legs or feet.…”
Section: Clinical Characteristicsmentioning
confidence: 92%
“…Trauma may promote the development of extremity melanoma [1,6,7] Gender Men may have a worse prognosis compared to women [4,27,16,93,21,20] Anatomic subsite The poorer prognosis of AM might be more closely related to the anatomical site than the histological subtype [5,22,29,28,31] Molecular pathology characteristics Chromosomal structural variations and copy number variations Compared to CM, AM has more chromosomal structural variations and CNVs Common copy number amplified genes include CCND1, GAB2, PAK1, TERT, YAP1, MDM2, CDK4, NOTCH2, KIT, and EP300; common copy number deletion regions, including those containing CDKN2A and NF1 and PTEN [23,44,46,51,47,61] Driver mutations the proportion of TWT mutations is higher in AM than in CM (38% vs. 11%) [60] Immune microenvironmental characteristics TILs AM has a suppressive immune microenvironment compared to CM (CD 8 + T cell, NK cells, and γδ T cells) [80,84] M2-Ms the density of M2-Ms is higher in the ALM tumor microenvironment compared to SSM [85] PD-L1 Lower levels of PD-L1 are present in AM than in chronic sun-damaged melanoma (31% vs. 62%)…”
Section: Clinical Characteristics Etiologymentioning
confidence: 99%